MENERAPKAN KONSEP DASAR BIMBINGAN DAN KONSELING PESERTA DIDIK DI SD GMIT 33 MORU 1 - Mariam Atamai; Heronike Mangmani, Jero sion E. Blgur, Yessy Mata, Petrus Mau Tellu Dony (TARBIYATUL ILMU: JURNAL KAJIAN PENDIDIKAN, 2025)
The aim of this study is to examine the apply Basic Concepts of Guidance and Counseling in Elementary Schools. This research uses a quantitative method. The data analysis technique was carried out through data reduction, data presentation, and conclusion drawing. This study was conducted at SD GMIT 33 MORU 1. The source of information in this research is Ms. Imelda Laumalay, S.Pd, who serves as a Classroom Teacher.The results of this study indicate that guidance and counseling in elementary school is an integral part of developing students’ potential optimally, both academically, personally, socially, and in terms of career. At the elementary level, the guidance and counseling approach is preventive and developmental, adapted to the growth stages of elementary-aged children.The basic concept of guidance and counseling includes an understanding of the characteristics of young children, the goals of services, the principles of implementation, and the role of the classroom teacher as the initial counselor. In addition, guidance services include activities such as information services, individual counseling, group counseling, and collaboration with parents.